2022
DOI: 10.3389/fnut.2022.1030344
|View full text |Cite
|
Sign up to set email alerts
|

Brick tea consumption and its relationship with fluorosis in Tibetan areas

Abstract: Brick tea-type fluorosis (BTF) due to a high intake of brick tea is possible in Tibetan populations, and dental fluorosis (DF) and skeletal fluorosis (SF) are its primary manifestations. To determine the prevalence of DF and SF and their relationships with brick tea intake in Tibetan populations, a literature review was conducted for studies published between 1994 and 2021. The available evidence revealed that brick tea may be produced from older stems and leaves of the tea plant and that the fluoride content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 89 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…Brick tea is a base material for making butter tea in Tibet, which a large number of Tibetan people drink every day. The harsh environment of the plateau has led to limited food sources for the local Tibetan people, who form the habit of drinking tea leaves as a satiation solution to digest greasy food and replenish vitamins [19]. The results of our dietary survey showed that the most consumed beverage, in both patients and controls in Qamdo, Tibet, was butter tea.…”
Section: Discussionmentioning
confidence: 81%
“…Brick tea is a base material for making butter tea in Tibet, which a large number of Tibetan people drink every day. The harsh environment of the plateau has led to limited food sources for the local Tibetan people, who form the habit of drinking tea leaves as a satiation solution to digest greasy food and replenish vitamins [19]. The results of our dietary survey showed that the most consumed beverage, in both patients and controls in Qamdo, Tibet, was butter tea.…”
Section: Discussionmentioning
confidence: 81%
“…Dental fluorosis represents a form of discolored teeth and serves as an early indicator of chronic fluorosis within the oral cavity. It is marked by the diminished enamel gloss in permanent teeth, often exhibiting a chalky or brownishyellow appearance, and irregular enamel defects become apparent in severe instances [1]. The impact of dental fluorosis extends significantly to the structure, morphology, and functionality of the teeth.…”
Section: Introductionmentioning
confidence: 99%
“…In the remaining cases, the sources of fluoride were toothpaste and inhalation of fumes containing this element. There are many scientific reports on fluoride content in various tea infusions, simultaneously attempting to assess the health risk, mainly in countries where tea consumption is high [12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Conclusions from these studies, in most cases, indicate that tea infusion is an important and insufficiently considered source of fluoride exposure, and its consumption, especially in larger quantities, may pose a potential health risk.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions from these studies, in most cases, indicate that tea infusion is an important and insufficiently considered source of fluoride exposure, and its consumption, especially in larger quantities, may pose a potential health risk. Of the 16 cited publications, 6 indicate that the risk assessment did not show a significant health risk from the consumption of tea infusions [22,27,29,32,33,35]. In addition, Ruxton and Bond [29] conclude that more significant dental health benefits could be achieved for the UK population if the average adult intake increased to four to five servings per day.…”
Section: Introductionmentioning
confidence: 99%